Use of the International League Against Epilepsy (ILAE) 1989, 2010, and 2017 Classification of Epilepsy in children in a low‐resource setting: A hospital‐based cross‐sectional study. Issue 3 (21st June 2020) - Sharma, Suvasini; Anand, Aakanksha; Garg, Divyani; Batra, Sakshi; Mukherjee, Sharmila B.; Patra, Bijoy; Aneja, Satinder
Abstract: Objectives: This cross‐sectional study was designed to test the applicability of the 1989, 2010, and 2017 International League Against Epilepsy (ILAE) classification of epilepsy in children from a resource‐limited setting in India. Methods: Classification of seizure types and syndromes was done through parental interviews and review of medical records in children with epilepsy aged one month to 18 years. Available investigations including EEG, MRI, and metabolic/genetic tests were used in classifying patients as per the 1989, 2010, and 2017 ILAE (level II‐epilepsy type) classification. We compared the proportion of children remaining unclassified by each scheme. Results: Seven hundred and twenty‐six children (436 males, mean age 6.4 ± 4.6 years) were enrolled. Using the 1989 ILAE classification, we were able to classify 95.7%, and 82.6% children by the 2010 scheme. The 2017 ILAE classification could classify all 726 children at level I (seizure type), 664 (91.0%) children at level II (epilepsy type), and an electroclinical syndrome could be identified in 409 (56.1%) of the children. An etiology could be identified in 75%, perinatal brain injury being the most frequent. West syndrome was the most common electroclinical syndrome, identified in 22.7% patients. The 1989 ILAE classification system was superior to the 2010 system ( P = .01) in epilepsy classification. There was no difference between the 1989 and 2017 schemes ( P = .31) or the 2010 and 2017 schemes ( P = .10). Significance: The 2017 ILAE classification, being multidimensional, allowed classification of children who could not undergo extensive evaluation due to economic constraints and also provided room for overlapping etiologies.